Hubungan Harga Diri (Self-Esteem) Dengan Kematangan Karier Mahasiswa Tingkat Akhir (Studi Deskriptif Kuantitatif pada Mahasiswa Program Studi Bimbingan dan Konseling Universitas Sanata Dharma) - Bernadheta Lely Utami; Maria Margaretha Sri Hastuti (Lembaga Pengembangan Kinerja Dosen, 2024)
This study aims to determine the level of self-esteem and career maturity of students in the final year of the Guidance and Counseling Study Program at Sanata Dharma University and determine the relationship self-esteem and career maturity of final year students of the Guidance and Counseling Study Program at Sanata Dharma University. This study used quantitative descriptive research with a correlational research design. The sample for this research consisted of 84 respondents consisting of final year students from the 2020 class of the Guidance and Counseling Study Program at Sanata Dharma University. Data collection techniques through surveys using Google forms. The number of valid items on the self-esteem scale is 36 items with a Cronbach's Alpha value of 0.914 and valid items on the career maturity scale are 38 with a Cronbach's Alpha value of 0.865. The results of study show that 1) the level of self-esteem of final year students is at a high level, 2) the level of career maturity of final year students is at a high level, and 3) there is a relationship between self-esteem and career maturity with significant (correlation coefficient, r=0.782, significance level 0.000 <0.05).